PENGARUH CITA RASA, KUALITAS PELAYANAN DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KEMBALI PADA USAHA SEBLAK DAPURAOS DI SUMBAWA - Khairiyanov, Khadijah Rahma; Sugiarto, Aris (Jurnal Nusa Manajemen, 2025)
This study aims to examine the influence of taste, service quality, and word of mouth on repeat purchase decisions at Seblak Dapuraos. The research method used is quantitative with a causal associative approach. Data were collected through questionnaires distributed to 100 respondents who are customers of Seblak Dapuraos. Data analysis was performed using multiple linear regression. The results of the study show that service quality and word of mouth have a positive and significant effect on repeat purchase decisions, while taste does not have a significant impact. These findings highlight the importance of good service quality and positive recommendations from consumers as the main drivers in enhancing customer loyalty for repeat purchases. Although taste is an important factor, it is essential to consider local characteristics and consumer preferences to optimize the customer experience.